Linguistic Manifestation of Concept of HEALTH in Contemporary Domestic Discursive Practices (Newspaper Corpora) - T. B. Radbil (Научный диалог)
This study addresses the issue of the linguistic explication of the concept of HEALTH within contemporary domestic media discourse. An investigation has been conducted into the functioning of the conceptual name — the lexeme ‘health’ — through linguistic material derived from contexts extracted from newspaper corpora within the National Corpus of the Russian Language. A corpus-based discursive analysis methodology was employed. Conceptual-metaphorical models that enrich the meaning of the concept and expand its semantic scope have been identified. It is demonstrated that the semantic transformations of the lexeme ‘health’ in its discursive realization reveal reflections on the understanding of the abstract concept of HEALTH as a resource, substance, physical object, mechanism, container, living entity, and more. It has been established that the augmentation of the semantic volume of the concept in contexts of attributive and genitive compatibility illustrates the dissemination of notions regarding health as a normal state or functioning of various entities across a wide array of spiritual, moral, psychological, emotional, social, political, economic, financial, industrial, natural, and cultural domains, including the operational sphere of devices, household items, instruments, and mechanisms. The study concludes with the assertion that the analyzed concept possesses a representative value potential linked to the cognitive dominance of normativity.